(untitled) (Nordic Journal of African Studies, 2010)
Political speech animation in Kenya can be a complicated affair allowing both the speaker and the audience to equally participate in speech animation. The audience could use the dialogue opportunity to re-direct what the speech topic should be thus assigning new topics or could even influence the direction of the ongoing speech topic. On the other hand the speech animator uses dialogue as a gauging device of his ideas and his own popularity as a member of political class, for control and coercion, engaging the audience that could otherwise feel bored and leave the rally, discussing stage managed topics, allowing the audience to lead directions in what could be an otherwise controversial topic leading to impoliteness on the part of the speech animator. Dialogue structure in Kenya is arguably present in most speeches though to a lesser degree in formal speeches but to a greater extent in extemporaneous oral speeches. Success in speech making has got to do with mastering how to sustain both the expected monologue structure but also the dialogic structure where the audience is passive and active at the same time.